Formulasi Sabun Transparan Minyak Ylang-Ylang dan Uji Efektivitas terhadap Bakteri Penyebab Jerawat - Febriyenti F.; Lisa Indah Sari; Rahmi Nofita (Jurnal Sains Farmasi & Klinis, 2014)
Ylang-ylang oil transparent soaps in three concentration i.e. 3.1 %, 3.85 % and 4.58 % have been formulated using virgin coconut oil (VCO), olive oil and stearic acid as a base soap reacted with NaOH as alkalin base. Transparent soap were tested for its identification, pH, wetting test, the foam on distilled water, the foam on hard water, skin irritation consumen preference test and micobiology test using the agar diffusion technique against bacterium cause of acnes like Staphylococcus epidermidis. The results showed that all formulas were stable for six weeks during storage conditions. Ylang-ylang transparent soap had medium antimicrobial activity (12-16 mm) against S. epidermidis. Statistical evaluation of pH, wetting test and micobiology test from formulas against control by using one way ANOVA had significant difference (p<0,05).